TINJAUAN STANDARISASI LABORATORIUM IPA SMPN SE-KABUPATEN DHARMASRAYA TAHUN PELAJARAN 2014/2015 - Hidayat, Rino - (Pendidikan Biologi, 2014)
Natural Science is one of the main subjects in the junior high school curriculum. This class is closely related to the facilities and infrastructures provided to optimize the efferts to active the goals. One of the facilities needed in natural science class is a standardized laboratory. This research was designed for figuring out the standardization of natural science laboratories in SMPNs in Kabupaten Dharmasraya covering the space of the lab, the forniture, the aducationalequipments, the educational media, and other utilities. This was a descriptive research which was intended to see, review and describe the object researched as it was during the researc. The data was collected through questionnaire which was administered to 10 respondents who were the natural science teachers in SMPNs in Kabupaten Dharmasraya. The data gotten was analyzed by using percentage technique. Based on the quistionnare distributed, it was revealed that the number of the laboratories having standardized rooms was 76,6 % , the number of standardized forniture available was in adequate category 100 %, and the number of others standardized utilities was in poor category 37 % in general, it was concluded that natural science laboratories in SMPNs in Kabupaten Dharmasraya viewed from standardization factor was in adequate category 68,7 %.